Mitogenomic evolutionary rates in bilateria are influenced by parasitic lifestyle and locomotory capacity - Ivan Jakovlić; Hong Zou; Tong Ye; Hong Zhang; Xiang Liu; Chuan-Yu Xiang; Gui-Tang Wang; Dong Zhang (Nature Communications, 2023)
Abstract The evidence that parasitic animals exhibit elevated mitogenomic evolutionary rates is inconsistent and limited to Arthropoda. Similarly, the evidence that mitogenomic evolution is faster in species with low locomotory capacity is limited to a handful of animal lineages. We hypothesised that these two variables are associated and that locomotory capacity is a major underlying factor driving the elevated rates in parasites. Here, we study the evolutionary rates of mitogenomes of 10,906 bilaterian species classified according to their locomotory capacity and parasitic/free-living life history. In Bilateria, evolutionary rates were by far the highest in endoparasites, much lower in ectoparasites with reduced locomotory capacity and free-living lineages with low locomotory capacity, followed by parasitoids, ectoparasites with high locomotory capacity, and finally micropredatory and free-living lineages. The life history categorisation (parasitism) explained ≈45%, locomotory capacity categorisation explained ≈39%, and together they explained ≈56% of the total variability in evolutionary rates of mitochondrial protein-coding genes in Bilateria. Our findings suggest that these two variables play major roles in calibrating the mitogenomic molecular clock in bilaterian animals.